Viscoplastic characterization and modeling of hybrid carbon fiber/carbon nanotubes reinforced composites. (15th August 2016) - Alipour Skandani, A.; Al-Haik, M.
Abstract: This investigation illuminates the effect of surface grown carbon nanotubes (CNTs) on the viscoplastic behavior of fiber reinforced plastics (FRPs). The study demonstrates the feasibility of growing CNTs on conventional woven carbon fibers without degrading the fibers structural properties. The subsequent hierarchal reinforcement was utilized to fabricate laminated FRPs. The viscoplastic behaviors of the hybrid composites were investigated through series of stress relaxation and creep tests at different thermomechanical environments. The results of the experimental tests were utilized to both construct and validate a phenomenological viscoplastic constitutive model of the hybrid FRPs. The experiments and the model predictions established that surface grown CNTs could enhance the composite resistance to viscoplastic deformation.